2019
DOI: 10.18203/2349-2902.isj20191904
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic subtotal cholecystectomy: a safe approach in difficult cholecystectomy

Abstract: Background: Laparoscopic cholecystectomy (LC) has been recognized as the new "gold standard" for the treatment of symptomatic gallstone disease. In order to prevent serious bile duct and vascular injuries, conversion is advocated for unclear anatomy at the Calot's. Our aim was to assess the safety and effectiveness of laparoscopic subtotal cholecystectomy (LSC) in difficult cholecystectomy in order to reduce the incidence of bile duct injury and conversion rates. Methods: An analysis of retrospectively collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Forty of the studies included in this review described the operative techniques performed. 13 30 , 32 40 , 42 45 , 47 53 , 55 57 Half of the patients had the posterior gallbladder wall left in situ (904/1,773, 51%). Different techniques were described for dealing with the cystic duct or gallbladder stump.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Forty of the studies included in this review described the operative techniques performed. 13 30 , 32 40 , 42 45 , 47 53 , 55 57 Half of the patients had the posterior gallbladder wall left in situ (904/1,773, 51%). Different techniques were described for dealing with the cystic duct or gallbladder stump.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty studies (1,418 patients) reported on long-term follow-up. 13 15 , 17 , 18 , 20 , 24 , 26 30 , 32 , 34 37 , 40 47 , 50 , 51 , 53 , 54 , 56 The median follow-up period was 22 months. Four deaths occurred in the period after thirty days following surgery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation